Reducing Energy Waste for Computers by Human-in-the-Loop Control - Munir, Sirajum; Stankovic, John A.; Liang, Chieh-Jan Mike; Lin, Shan (TETC (IEEE Transactions on Emerging Topics in Computing), 2013)
While current Cyber Physical Systems (CPS) act as the bridge between humans and environment, their implementation mostly assumes humans as an external component to the control loops. We use a case study of energy waste on computer workstations to motivate the incorporation of humans into control loops. The benefits include better response accuracy and timeliness of CPS systems. However, incorporating humans into tight control loops remains a challenge as it requires understanding complex human behavior. In our case study, we collect empirical data to understand human behavior regarding distractions in computer usage and develop a human-in-the-loop control that can put workstations into sleep by early detection of distraction. Our control loop implements strategies such as an adaptive timeout interval, multilevel sensing, and addressing background processing. Evaluation on multiple subjects show an accuracy of 97.28% in detecting distractions, which cuts the energy waste of computers by 80.19%.